2008
DOI: 10.1111/j.1600-0625.2008.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐interleukin‐31‐antibodies ameliorate scratching behaviour in NC/Nga mice: a model of atopic dermatitis

Abstract: Background: Interleukin-31 (IL-31), a novel cytokine, is upregulated in atopic dermatitis skin lesions in humans and skin lesions in the NC ⁄ Nga mice, a murine model for atopic dermatitis.Objective: Here, we investigated the effect of a monoclonal IL-31 antibody on scratching behaviour, weight gain and dermatitis in NC ⁄ Nga mice.Methods: Mice were divided into three groups, n = 10 in each group. Mice were given monoclonal IL-31 ratanti-mouse antibody 10 mg ⁄ kg or albumin intraperitoneally every fifth day fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(164 citation statements)
references
References 48 publications
(70 reference statements)
4
141
1
5
Order By: Relevance
“…1A). This Ab has also been used in vivo to ameliorate the scratching behavior of NC/Nga mice that spontaneously develop AD (15). We further confirmed the ability of this Ab to neutralize IL-31 activity in vivo using a biological readout of hair loss in IL-31-treated animals.…”
Section: Anti-il-31 Neutralizing Absupporting
confidence: 60%
See 2 more Smart Citations
“…1A). This Ab has also been used in vivo to ameliorate the scratching behavior of NC/Nga mice that spontaneously develop AD (15). We further confirmed the ability of this Ab to neutralize IL-31 activity in vivo using a biological readout of hair loss in IL-31-treated animals.…”
Section: Anti-il-31 Neutralizing Absupporting
confidence: 60%
“…Investigation of IL-31 transgenic mice showed that overexpression of IL-31 resulted in the development of AD-like lesions, and that IL-31 expression was highly associated with Th2-skewed T cells (1). In a nontransgenic murine model of spontaneous AD development, increased levels of IL-31 mRNA were associated with scratching behavior (24,25), and subsequent inhibition of scratching was achieved using a neutralizing anti-IL-31 mAb (15). Finally, increased levels of IL-31 mRNA have been associated with samples from human AD patients (2,5), and these IL-31 levels were further shown to correlate with increases in IL-4 and IL-13 (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, overexpression of IL-31 in transgenic mice results in a severe pruritus, alopecia, and skin lesions (1). Moreover, neutralization of IL-31 has been shown to ameliorate scratching behavior in a mouse model of atopic dermatitis (12). Recent studies suggest that IL-31 signaling is required to limit Th2 cytokinedriven inflammation in the lung and that a complete genetic loss of IL-31RA might result in increased activity and signaling by oncostatin M (OSM) via OSMR␤ (13).…”
Section: Interleukin 31 Receptor ␣ (Il-mentioning
confidence: 96%
“…In addition, increased IL-31 and IL-31RA levels have been found in Th2-related allergic diseases, such as atopic dermatitis (39), which is characterized by the polarization of antigen-presenting cells and activation of a Th2 response (40). In a mouse model of atopic dermatitis, increased IL-31 transcripts were associated with scratching behavior (41), whereas a recent study showed that anti-IL-31 neutralizing antibody reduces scratching behavior and dermatitis in mice (12). Based on an accumulating understanding of IL-31 signaling and atopic dermatitis, our findings suggest that signaling induced by Th2 cytokines is critical in regulating IL-31/IL-31RA interactions involved in inflammatory and remodeling responses.…”
Section: Sea-challenged Il-13r␣1mentioning
confidence: 96%